Studi Efek Bentuk Butiran Ukuran Bervariasi Terhadap Sifat Kemagnetan Magnet Permanen - D. Tarihoran; A. Manaf (Indonesian Journal of Physics, 2002)
Stoner-Wohlfarth (SW) theory shows a deviation of around 30-40% compared to measurement results of a permanent magnetic material with nanometer-sized grains. This is because this theory neglects the interacting grain factor. This research modifies the SW theory by calculating the grain interacting effect. The modification is made by assuming theinteracting energy of a single domain ellipsoidal grain is focused at the edge of the grain. The SW grain in this calculationis modeled as a box in the ellipsoid. The result shows that the interacting effect increases remanent polarization drasticallyand decreases the coercive field value when grain size reaches 20% of the unitial single domain grain (~100 nm). For material with Nd2Fe14B phase, the optimum coercive field value and remanent polarization that produce maximum energy product (BH)max occurs in a material with ~5 nanometer-size grains. There is an appropriate qualitative result between the calculation and measurement.